Proximate composition of Nahar (mesua ferrea) leaves and antibacterial assay of its extracts - Idris Adewale, Ahmed; Elwathig Mohamed, Saeed Mirghani; Suleyman Aremu, Muyibi; Jamal Ibrahim, Daoud; Maryam Abimbola, Mikail (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.